IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH ENGLISH NEWSPAPER ARTICLE AT EIGHTH GRADE OF MTS AL MUNAWWARAH MEDANG DERAS - Lestary, Febri (BRIGHT VISION Journal of Language and Education, 2022)
This research was aimed to know and to describe how the English newspaper articles can improve the students’ vocabulary mastery by using English newspaper articles at  eighth grade of MTs S Babul Ulum Medan Labuhan in 2018/2019 academic year. The method used in this study was Classroom Action Research (CAR). The subject of this research consisted of 30 students of VIII-1. In this case the teacher of MTS Al Munawwarah as an observer and collaborator.  The  research  conducted  in  two  cycles,  cycle  I  consist  of  t wo meetings and cycle II was one meeting. The research was conducted as follow; planning, acting, observing, and reflecting. The data used in this research such as: Pre-test and Post-test, observation sheet, interview sheet, diary notes, and documentation. The data were gathered through qualitative and quantitative data. The qualitative data were gained by analysing the interview, observation result, diary notes and documentation. Then, quantitative data were obtained from the students’ vocabulary score of pre-test, post-test I, and post-test II. The result of this research showed that there was improving of students’ vocabulary  mastery through  English  newspaper  articles.  Most  of the  students achieved a good score at the end of every cycle. The passing grade of English lesson was 75 (seventy five). The mean of the pre-test was 42,66. The mean of the first cycle was 70,50. The mean of second cycle was 86,33. It was indicated that the scores and the mean in second cycle were better than the first cycle. The percentage of students who got point 75or more also grew up. It means that there was an improving about 43,33%. The post-test of cycle II, students who got point 75or more there were 30 students (100%) and the improving was about 56,67%. For the total improving of the students’ score from pre-test to post-test of cycle II was 100%. In other words, the students’ vocabulary mastery improved and became very well in the first meeting to the next meeting. Related to observation result and the interview, showed that got positive responses from the students. The students were more active, enthusiasm, motivated in teachinglearning process. In addition, from English newspaper articles, the students could develop their own personal vocabulary  and  get  much  variation  of  vocabularies.  Thus,  it  was  found  that through English newspaper articles can improve the students’ vocabulary mastery.